1980
DOI: 10.1111/j.1365-2052.1980.tb01505.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative aspects of biochemical polymorphism in the blood of Caprinae species and their hybrids

Abstract: Biochemical variation at 14 blood loci was reviewed, and specific features compared experimentally in sheep Ovis aries, mouflon Ovis mwimon, goat Capra hircus, aoudad Ammotragus lervia and in 2 stillborn aoudad X goat hybrids. Variation at 3 loci was also studied in dall sheep Ovis dalli, bighorn sheep Ovis canadensis and rocky mountain goat Oreamnos americanus. Haemoglobin C production in an anaemic Hb AB mouflon and in mouflon X sheep hybrids was examined. Mouflon differ from domestic sheep in that synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Genetic variation studies have been conducted concerning ME in domestic animals. In the studies performed on sheep (Tucker and Clarke 1980;Yaman and Tucker 1981), S, F, and FS bands were observed, as was the case in the present study of cat breeds. In a study performed on the goats of Argentina (Deza et al 2000), A, AB, and B bands (similar to those bands observed in cats) were observed.…”
Section: Resultssupporting
confidence: 64%
“…Genetic variation studies have been conducted concerning ME in domestic animals. In the studies performed on sheep (Tucker and Clarke 1980;Yaman and Tucker 1981), S, F, and FS bands were observed, as was the case in the present study of cat breeds. In a study performed on the goats of Argentina (Deza et al 2000), A, AB, and B bands (similar to those bands observed in cats) were observed.…”
Section: Resultssupporting
confidence: 64%
“…The samples were despatched by air to England and were tested as soon as possible after arrival. The tests comprised identification of red cell antigens and of red cell and plasma protein and enzyme variants (Tucker, 1971(Tucker, ,1975(Tucker, , 1976Tucker & Clarke, 1980). Red cell antigen factors controlled by the A, B, C, D , M , and R-Z loci were examined with 16 different reagents.…”
Section: Methodsmentioning
confidence: 99%
“…When goat red cell lysates are subjected to electrophoresis and stained with a protein stain, the more anodal visible zone has been given the designation of 'X' protein (Tucker & Clarke, 1980). Two different phenotypes of 'X' protein have been described in goats by these authors.…”
Section: 'X' Proteinmentioning
confidence: 99%
“…We have also detected two different 'X' protein phenotypes. One of them, perhaps equivalent to the three-banded one described by Tucker & Clarke (1980), consists of one major and two minor bands and has been designated X+ protein.…”
Section: 'X' Proteinmentioning
confidence: 99%